Latin America in the Post-Chavez Era : The Security Threat to the United States - Fleischman, Luis, 1959- (Book collections on Project MUSE., 2013)
Hugo Chavez has recently undergone three surgeries for cancer, prompting much speculation and anxiety about the impact of his death. What will a post-Chavez future look like, not only in Venezuela but also in the region"" In Latin America in the Post-Chavez Era, Luis Fleischman examines Chavez's highly controversial Bolivarian revolution, which has expanded beyond Venezuela to other countries in South America and whose sphere of influence also extends to Central America and the Caribbean. Across Latin America, Chavez has financially supported political candidates or presidents in office dedica